An Analysis on Investment, Government Expenditures, and Gross Domestic Revenue on Employment in North Sumatera - Syafaruddin Munthe (Universitas Negeri Medan, 2018)
Employment is basically a problem which is faced by all regions, but its intensity may vary, based the factors which influence it. Employment exists because of investment and attempts to extend employment because of other factors such as inflation, interest rate, exchange rate, government expenditures, and PDRB (Gross Domestic Revenue). The objective of the research was to analyze the influence of exogenous variables on endogenous variables such as employment, inflation, interest rate, exchange rate, investment, government expenditures, and PDRB. The research used quantitative analysis by using coherent secondary data from 1985 until 2015 obtained from BPS (Central Bureau of Statistics) ofNorth Sumatera and Bank Indonesia. The data were analyzed by using path analysis model. The result of the research showed that exogenous variables simultaneously had significant influence on endogenous variables in each equation model. The variables of investment, government expenditures, gross domestic revenue, inflation, and interest rate did not have any significant influence on the variable of employment. Meanwhile, the variable of exchange rate had positive and significant influence on the variable of employment. Therefore, it is recommended that the variable of exchange rate became theattention of the North Sumatera Provincial Administration.